Characteristics Biolubricant Enriched with Nanoparticle Additives: a Review - Sholiha, Zhahra Hanif; Jatisukamto, Gaguk (Universitas Negeri Malang, 2020)
The engine movement mechanism is a system composed of machine elements that contact or rub against each other between these surfaces. Surfaces that rub against each other will cause a friction force that causes wear on the surface, so it requires energy to fight the friction force. Lubricants are needed to reduce friction and reduce wear rates, where lubricants are generally made of mineral materials. Lubricants made from synthetic materials are non-renewable and cause environmental problems. The development of biolubricants as lubricating materials based on animal fats or vegetable oils is continuously being carried out. This study aims to observe the potential of biolubricants based on reviews from various previous research journals. The use of additives in biolubricants is also studied whether the addition of these additives can improve the characteristics of biolubricants. This study shows that the addition of certain additives to biolubricants can improve the characteristics of biolubricants.